(untitled) (London Journal of Research In Science: Natural and Formal, 2025)
CO? exchanges between continents, oceans and atmosphere are analyzed over the last 50 years, correcting for the importance of agriculture and forestry. Global crops capture and store an average of 40.4 GtCO?/year, a flow greater than fossil emissions, both followingpopulation growth. The mineralization of agricultural and forestry biomasses releases 12.3GtCO?/year, leading to a stable continental balance of about 7.2 GtCO?/year emitted. Contrary to previous studies, this one shows that the ocean has become an increasingly strong source of CO?, from the neutrality of the 1970s to reaching an average of 10.4 GtCO?/year over the last decade. Over the half-century, the ocean has contributed 55% to the increase in atmospheric CO? concentration, with the remainder coming from the continents. These results challenge common assessments that underestimate the role of crop plants as CO? sinks and, as therefore, wrongly attribute to the ocean a role in absorbing anthropogenic emissions.